Engineering Neural Tissue from Human Pluripotent Stem Cells Using Novel Small Molecule Releasing Microspheres. Issue 12 (17th September 2018) - De la Vega, Laura; Karmirian, Karina; Willerth, Stephanie Michelle
Abstract: Here a novel technique for engineering neural tissue consisting of motor neurons by combining human‐induced pluripotent stem cells (hiPSCs) with small molecules releasing microspheres is demonstrated. First, the small molecule purmorphamine (puro) is successfully encapsulated into poly ε‐caprolactone (PCL) microspheres using a single emulsion oil‐in‐water (o/w) method for the first time with an efficiency of (84% ± 2.12%). These microspheres release 91% ± 1.7% of the encapsulated puro in a controlled fashion over 46 days. Puro microspheres, along with previously characterized retinoic acid (RA) releasing microspheres, are then incorporated into hiPSC aggregates to engineer neural tissue. The combination of puro and RA microspheres promotes hiPSC differentiation as indicated by the expression of multiple neural markers, including the neuronal marker β‐tubulin III (βT‐III), and the transcription factor Olig2 (7.69 ± 8.38%) on day 28. These tissues express the motor neuron marker HB9 (24.85 ± 4.51%) on day 35, and the mature motor neuron marker ChaT (12.35 ± 4.17%) on day 60. These engineered tissues can be used for regenerative medicine applications such as treating spinal cord injury (SCI), disease modeling, and drug screening. Abstract : Controlled release of the small molecule morphogen purmorphamine from poly ε‐caprolactone microspheres is characterized. Then, engineered neural tissues are produced by forming aggregates of human‐induced pluripotent stem cells in the presence of drug loaded microspheres. These engineered neural tissues express the motor neuron markers HB9 and ChaT.